Analysis Plots of The Novel Harry Potter and The Philosopher’s Stone – J.K Rowling (1997) - Muhammad Zahid (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This study uses a qualitative research method to determine the understanding of the plot in the novel Harry Potter and The Philosopher's Stone – J, K Rowling (1997) for learning English. The data is analyzed using a qualitative approach by the researcher. Stone – J, K Rowling (1997) was used as a research instrument, the novel was understood to contain the plot, the plot became the focus of this research. The author concludes the novel of Harry Potter and as a sample The Philosopher's Stone – J, K Rowling (1997), Method of The writer uses a story line, so it can be concluded that the novel Harry Potter and the Philosopher's Stone – J, K Rowling (1997) can motivate us to learn English because of using this novel learning process be exciting stories, while the author's difficulty in understanding Harry Potter and The Philosopher's Stone – J, K Rowlin. plot (1997) because the plot is very unpredictable, this novel tells about the adventures of a teenage wizard namely Harry Potter and his friends, Ronald Weasley and Hermione Granger. All of them are students at Hogwarts School of Witchcraft and Wizardry. Harry will defeat the evil black wizard Lord Voldemort, whom his ambition becoming immortal, conquering the magic realm, take over non-magical people, and annihilate anyone who gets in his way, especially Harry Potter.